Romantic and Neo-Romantic in W. B. Yeats’s Poetry - E. A. Markova (Научный диалог)
The question of categories “romanticism” and “romantic” in connection with the works by the Irish poet and playwright W. B. Yeats is considered. The analysis of existing works on this topic reveals conceptual and terminological lacunae. The necessity of using the term neo-romantic when studying Yeats’s poetry is substantiated. The author raises the question of the perception of the concepts of “romantic (noun)” and “romantic (adjective)” by the poet himself (“the last romantic,” “romantic Ireland”), as well as romanticism as a cultural and historical era. The novelty of the study is seen in the analysis of Yeats’s neo-romanticism, which is understood as a new version of romanticism, “anti-romantic romanticism,” which abandoned the “old romantic dreaminess” of the early 19th century and its peculiar language. The author of the article believes that Yeats’s neo-romanticism is based on the socio-cultural foundations of the early 20th century (“end of the century,” “death of God,” acceleration of the process of secularization, social cataclysms, such as the Easter uprising in Ireland, the First world war, the revolution in Russia) and acquires the appropriate language. It is shown that the rhythms and pulsations of the era found their expression in the “passionate syntax” - a special style of writing developed by Yeats. Two poems are analyzed (“Adam’s Curse” and “No Second Troy”), written in the “middle” period of the poet’s work, exactly when his style began to change noticeably.